Relevance of the Resourceful Human Management Concept in Employee Management at PT Bank Central Asia, Tbk - Vicky Alvindra Pratama; Eddy Madiono Sutanto (Master of Management, School of Business and Management, Petra Christian University, 2024)
Employee management with the concept of resourceful humans is a new paradigm that holds immense potential. It focuses on developing potential, knowledge, and capabilities to significantly increase employee productivity and organizational contribution. This concept is yet to be fully implemented at PT Bank Central Asia. This research aims to uncover the most suitable concept of resourceful humans for application at PT Bank Central Asia, one that can bring about substantial improvements. The research employs a qualitative descriptive method with data collection through interviews and a systematic and comprehensive data analysis model. Effective employee management is crucial for ensuring employees have the ability and knowledge, providing opportunities for development and innovation, and fostering good relationships between employees and the company to create a conducive work environment that can motivate employees. Resourceful human management emerges as a promising concept for PT Bank Central Asia.